The Relationship of Mother Characteristics and Husband Support With The Risk of Postpartum Blues In Postpartum Mothers - Ni Made Ari Febriyanti (PLACENTUM: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2021)
Background: Childbirth is an important event a waited by women. Some adjustments are needed by women in facing her new role as a mother. Psychological disorders that are often experienced by postpartum mothers are called postpartum blues. The incidence of postpartum blues abroad is quite high 26-85% and if this is not treated it will continue to be postpartum depression. The purposeuofithisrstudyuwasotoidetermineythearelationship between maternal characteristics and husband support with the risk of postpartum blues in the postpartum mothers.Design and method: The design of this study was cross-sectional analytics and was carried out at the East Denpasar Health Center I with a large sample of 30 respondents who visited the third to tenth day and met the inclusion criteria. The sampling technique of this research is accidental sampling. The independent variables in this study are the characteristics (age, education, occupation, parity), husband support and the dependent variable is the risk of postpartum blues. Data was collected using the Edinburgh Posnatal Depression Scale (EPDS) questionnaire and data analysis was carried out in stages including univariate and bivariate (chi square).Result: The results showed that most (73,3%) respondents did not experience symptoms of postpartum blues and almost half (26,7%) respondents experienced symptoms of postpartum blues. Bivariate results showed a significant relationship between education (p=0,00), parity (p=0,00), husband support (p=0,00) and the risk of postpartum blues.Conclusion: There is relationship between education, parity, husband support, and the risk of postpartum blues among postpartum mothers.